Network structures and their role in the development of innovative and intellectual activity of business entities - D. V. Ovodenko; N. M. Tyukavkin (Вестник университета)
The article studies the level of innovative development of economic entities, which is due to the fact that in recent years it is significantly influenced by various directions of innovation and intellectual activity of economic entities. New technological opportunities are the basis for national innovation system transformation and networking environment formation, which will allow more effective use of management technologies for developing innovation and intellectual activity subjects, contributing to the emergence of complex innovative structures and management systems. The topic of the study is aimed at identifying and assessing the role of network structures in the development of innovation and intellectual activity of economic entities, which is a significant factor for the economic entity in connection with the realization of the importance of creating an integrative educational environment as the most effective form of educational processes implementation in the future. The conducted research and study of the scientists’ materials, who investigated the network structures role in the development of innovation and intellectual activity of business entities, as well as their impact on the development of Russian regions and the country’s economy as a whole, have shown that new mechanisms and ways of assessing the network structures role and systematizing the approaches of various scientists and specialists, who study and have studied this problem, are necessary.